2018
DOI: 10.1002/hyp.13142
|View full text |Cite
|
Sign up to set email alerts
|

Is there a limit to bioretention effectiveness? Evaluation of stormwater bioretention treatment using a lumped urban ecohydrologic model and ecologically based design criteria

Abstract: In this study, we developed the urban ecohydrology model (UEM) to investigate the role of bioretention on watershed water balance, runoff production, and streamflow variability. UEM partitions the land surface into pervious, impervious, and bioretention cell fractions. Soil moisture and vegetation dynamics are simulated in pervious areas and bioretention cells using a lumped ecohydrological approach.Bioretention cells receive runoff from a fraction of impervious areas. The model is calibrated in an urban headw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…We utilize an ecohydrological model (the Bucket Grassland Model [BGM]) (Istanbulluoglu et al, 2012; Yetemen, Istanbulluoglu, Flores‐Cervantes, et al, 2015), to understand the roles of geographical, climatological, soil, and vegetation factors affecting SMV on two different landform shapes. BGM has been extensively used in ecohydrological studies (Caracciolo et al, 2014; Naseem et al, 2016; Srivastava et al, 2019; Tang et al, 2019; Wright et al, 2018; Yetemen et al, 2015,b; Zhou et al, 2013) and was found to represent SMV accurately. In particular, Yetemen et al (2015,b) applied the BGM model to the SNWR site that we use as a guide to setup our experiments, and were able to successfully reproduce daily runoff and soil moisture observations (Nash‐Sutcliffe efficiency of 0.76) as well as vegetation extent and seasonality.…”
Section: Methodsmentioning
confidence: 99%
“…We utilize an ecohydrological model (the Bucket Grassland Model [BGM]) (Istanbulluoglu et al, 2012; Yetemen, Istanbulluoglu, Flores‐Cervantes, et al, 2015), to understand the roles of geographical, climatological, soil, and vegetation factors affecting SMV on two different landform shapes. BGM has been extensively used in ecohydrological studies (Caracciolo et al, 2014; Naseem et al, 2016; Srivastava et al, 2019; Tang et al, 2019; Wright et al, 2018; Yetemen et al, 2015,b; Zhou et al, 2013) and was found to represent SMV accurately. In particular, Yetemen et al (2015,b) applied the BGM model to the SNWR site that we use as a guide to setup our experiments, and were able to successfully reproduce daily runoff and soil moisture observations (Nash‐Sutcliffe efficiency of 0.76) as well as vegetation extent and seasonality.…”
Section: Methodsmentioning
confidence: 99%
“…The literature has similar variability in DARs analyzed. For studies that reported this metric, values ranged from 1% to 25% (Boancă et al 2018;Li et al 2009;Stander et al 2010;Wright et al 2018). More commonly, design standards are based on depths of runoff that should be captured and/or treated by a stormwater control measure (McPhillips et al 2020).…”
Section: Green Stormwater Infrastructure Modelingmentioning
confidence: 99%
“…These practices can also improve water quality (Johnson and Hunt 2019), but the focus of this paper is the hydrologic benefits. Research using either field monitoring (Li et al 2009;Stander et al 2010;Winston et al 2016) or numerical modeling (Jennings 2016;Olszewski and Davis 2013;Sun et al 2019;Wadzuk et al 2017) has shown that, when properly designed and maintained, bioretention areas can reduce runoff volumes and peak flow rates, potentially improving stream integrity (Wright et al 2018). A number of factors affect bioretention performance, including design choices (e.g., surface area, soil depth, infiltration capacity) (Jennings 2016;Lewellyn and Wadzuk 2019) and climate (Cook et al 2019;Hung et al 2020;Jennings 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations